2022
DOI: 10.1111/mec.16543
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics reveals contrasting patterns of connectivity in two newt species (Lissotriton montandoniandL. vulgaris)

Abstract: Human-induced habitat loss and deterioration are shaping connectivity patterns of numerous taxa around the globe. When natural levels of connectivity are disrupted, many potentially synergistic factors (e.g., demographic, genetic and environmental) can jeopardize the future of taxa (Crooks & Sanjayan, 2006;Richardson et al., 2016). In the short-term, isolated populations become more prone to extirpations through random demographic or environmental events as well as the deleterious genetic consequences of incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 90 publications
(148 reference statements)
2
25
0
Order By: Relevance
“…While lower sensitivity to anthropogenic landscape features fits with their hypothesis for a generalist species and is supported by other studies of amphibians (Nowakowski et al, 2018;Pabijan et al, 2020;Pyron, 2018), Antunes et al (2022) found that local N e was significantly lower for L. vulgaris than L. montandoni. For a widespread species to show lower resistance to anthropogenic landscape features but to have less genetic connectivity compared to a range-restricted species is surprising.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…While lower sensitivity to anthropogenic landscape features fits with their hypothesis for a generalist species and is supported by other studies of amphibians (Nowakowski et al, 2018;Pabijan et al, 2020;Pyron, 2018), Antunes et al (2022) found that local N e was significantly lower for L. vulgaris than L. montandoni. For a widespread species to show lower resistance to anthropogenic landscape features but to have less genetic connectivity compared to a range-restricted species is surprising.…”
supporting
confidence: 84%
“…Illegal logging damages ecosystems and contributes to unsustainable markets that value profit over long‐term quality and conservation of biodiversity. If forest cover has continued to diminish since the time of their sampling, findings from Antunes et al (2022) suggest these two species may have suffered local extinctions.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations